2021
DOI: 10.1101/2021.07.26.21261142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking Cryptic SARS-CoV-2 Lineages Detected in NYC Wastewater

Abstract: Tracking SARS-CoV-2 genetic diversity is strongly indicated because diversifying selection may lead to the emergence of novel variants resistant to naturally acquired or vaccine-induced immunity. To monitor New York City (NYC) for the presence of novel variants, we amplified regions of the SARS-CoV-2 Spike protein gene from RNA acquired from all 14 NYC wastewater treatment plants (WWTPs) and ascertained the diversity of lineages from these samples using high throughput sequencing. Here we report the detection … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 55 publications
(45 reference statements)
2
43
0
Order By: Relevance
“…This “chain reaction” of host jumping could potentially lead to remarkably high diversity in the adaptation to ACE2 from various host species. Consistent with this possibility, numerous mutations were identified in the spike protein of SARS-CoV-2 RNA fragment amplified from wastewater samples ( Smyth et al, 2021 ).…”
Section: Discussionmentioning
confidence: 75%
“…This “chain reaction” of host jumping could potentially lead to remarkably high diversity in the adaptation to ACE2 from various host species. Consistent with this possibility, numerous mutations were identified in the spike protein of SARS-CoV-2 RNA fragment amplified from wastewater samples ( Smyth et al, 2021 ).…”
Section: Discussionmentioning
confidence: 75%
“…Using a relatively conservative SNV calling pipeline and lineage detection method, we tracked the spread of SARS-CoV-2 lineages in wastewater between March 2020 and July 2021 across three cities in the province of Quebec. Although WW sequencing could be used to detect novel mutations or variant lineages not found in clinical samples (Smyth et al 2021), here we focused on identifying known variants. Consistent with a similar study in the US, we found that sequencing coverage in WW was dependent on viral load, as measured by the qPCR cycle threshold (Ct) value (Baaijens et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the United States have shown that the dominant SARS-CoV-2 variants observed in clinical samples are largely mirrored in wastewater sequences (Crits-Christoph et al 2021; Baaijens et al 2021). Wastewater also has the potential to capture mutations and variant lineages not observed in human clinical samples, potentially including animal reservoirs (Smyth et al 2021). However, more studies are required to assess the sensitivity and spatio-temporal resolution of wastewater sequencing in comparison to clinical sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater-based surveillance is a complementary, cost-effective approach to clinical sequencing, which has gained significant attention throughout the COVID-19 pandemic (Jahn et al 2021; Hillary et al 2021; Peccia et al 2020; Smyth et al 2021; Mishra et al 2021). Given that SARS-CoV-2 is shed in faeces by more than 50% of infected people (Foladori et al 2020), it can be recovered from wastewater, its RNA extracted, and its presence and quantity in a wastewater catchment determined using RT-qPCR (Farkas et al 2020), with trends generally tracking the rise and fall of corresponding clinical cases (Peccia et al 2020; Hillary et al 2021; Wade et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the recovery of SARS-CoV-2 genomes from wastewater has opened up the possibility of detecting and tracking circulating SARS-CoV-2 variants (Jahn et al 2021; Hillary et al 2021; Peccia et al 2020; Smyth et al 2021; Brown et al 2021). Such an approach is particularly attractive for population-level insights during periods of high prevalence, especially if capacity constraints reduce the proportion of sequenced positive RT-qPCR tests.…”
Section: Introductionmentioning
confidence: 99%